Novel Immune Cell-Based Therapies to Eradicate High-Risk Acute Myeloid Leukemia - Limongello, Roberto; Marra, Andrea; Mancusi, Antonella; Bonato, Samanta; Hoxha, Eni; Ruggeri, Loredana; Hui, Susanta; Velardi, Andrea; Pierini, Antonio (Frontiers in Immunology, 2021)
Adverse genetic risk acute myeloid leukemia (AML) includes a wide range of clinical-pathological entities with extremely poor outcomes, thus novel therapeutic approaches are needed. Promising results achieved by engineered chimeric antigen receptor (CAR) T cells in other blood neoplasms, have paved the way for the development of immune cell-based therapies for adverse genetic risk AML. Among these, adoptive cell immunotherapies with single/multiple CAR-T cells, CAR-natural killer (NK) cells, cytokine-induced killer cells (CIK) and NK cells are subjects of ongoing clinical trials. On the other hand, allogeneic hematopoietic stem cell transplantation (allo-HSCT) still represents the only curative option for adverse genetic risk AML patients. Unfortunately, high relapse rates (above 50%) and associated dismal outcomes (reported survival ~10-20%) even question the role of current allo-HSCT protocols and emphasize the urgency of adopting novel effective transplant strategies. We have recently demonstrated that haploidentical allo-HSCT combined with regulatory and conventional T cells adoptive immunotherapy (Treg-Tcon haplo-HSCT) is able to overcome disease-intrinsic chemoresistance, prevent leukemia-relapse and improve survival of adverse genetic risk AML patients (~80%). Our approach can also be safely extended to older (> 60 years-old) and frail patients through a modified myeloablative conditioning regimen that includes total marrow/total lymphoid irradiation instead of total body irradiation. Such approach reduces toxicity while it preserves a powerful Graft-versus-Leukemia effect. In this Perspective, we briefly review the recent advancements with immune cell-based strategies against adverse genetic risk AML and discuss how such approaches could favourably impact on patients’ outcomes.